Investigating the Effects of Work-Family Conflict on Turnover Intention of ICT Employees in Malaysia - Lee, Lai Meng; Gan, Su Wan; Chia, Yong Sheng (Makara Human Behavior Studies in Asia, 2023)
With the intensified focus on information and communication technology (ICT) as a driver of the Malaysian economy, pressure will increase on the recruitment and retention of ICT employees. However, work overload and conflict with family roles may lead to a higher level of turnover intention among ICT employees. The objective of this study is to investigate the predicting effects of all forms of work-family conflict (time-based, strain-based and behavior-based) on turnover intentions. This quantitative cross-sectional study utilizes primary data collected from 200 employees from ICT companies in the Klang valley using purposive sampling. Various statistical analyses such as correlation and multiple regression analyses were conducted to analyze the collected data with the SPSS statistical package. The findings indicate that all forms of work to family conflict and family to work conflict had effect on turnover intentions except for time-based form of family to work conflict (TFWC). This study has significance for the management of ICT companies in Malaysia as it provides human resource managers with a better understanding of their employees needs in order to devise better strategies to reduce turnover rate. This study also addressed some limitations, implications and recommendations for future research.